Two main stream methods analysis and visual 3D genome architecture. (June 2019) - Fu, Suolan; Zhang, Linlin; Lv, Jiapei; Zhu, Bijun; Wang, Wei; Wang, Xiangdong
Abstract: Multi-dimensions dynamics of the genome play important roles in the maintenance of cell function, regulation of transcriptional signals and occurrence of diseases. With rapid development of methodologies, the genome organization and structure are found as three-dimensional (3D) or with dynamic changes (4D), and regulated by a large number of factors. The present article aims to overview the 3C derivation method Hi-C and ChIA-PET assay technologies coupled with newdata analysis methods, capture the spatial interactions between different loci across the entire genome, reveal the regularity of the genome spatial structure. Its relationship with gene regulation is for better understanding of the spatial structure of the genome. From two mainstream methods of ChIA-PET and Hi-C, we obtain some special proteins mediated chromatin interaction and whole genome chromatin interaction, transform frequency relation to distance relation for further coordinates, and predict 3D architecture. ChIA-PET method more focuses on one protein binding effect of chromatin activities, while Hi-C method more comprehensive with challenges in data process. Data of chromatin interaction, thermogram, and chromatin spatial structure from integrated analyses of two methods indicates the further need of deep mining and exploration.